Intramedullary meningioma of spinal cord: Case report of a rare tumor highlighting the differential diagnosis of spinal intramedullary neoplasms - Ishita Pant; Sujata Chaturvedi; Vinod Kumar Singh Gautam; Rima Kumari (Wolters Kluwer Medknow Publications, 2014)
A 15-year-old male presented with progressive weakness of both lower limbs with urinary incontinence. Magnetic resonance imaging revealed a spinal intramedullary mass at D7-D8 level. The child was operated with a preliminary diagnosis of an intramedullary tumor. Atypical ependymoma and astrocytoma were considered in the differential diagnosis. Per- and post-operative histopathological examination reported the case as transitional meningioma (WHO Grade I). Spinal intramedullary meningiomas being a rare entity may be confused with other common intramedullary tumors. Though, rare still the possibility of an intramedullary spinal mass of being a meningioma does exist and therefore should be considered in the differential diagnosis of intramedullary tumors.